IMPACT AND RISK MITIGATION OF THE UNITED STATES DEFERRED PROSECUTION AGREEMENT ON MULTINATIONAL CORPORATE COMPLIANCE - Ma Jiao,; Wong Hua Siong,; Azwina Wati binti Abdull Manaf, (Journal of Islamic, Social, Economics and Development, 2024)
Deferred Prosecution Agreements (DPAs) in the United States (U.S.) criminal justice system, along with their related provisions, effectiveness, and legal consequences, can have significant impacts on the cross-border operations, compliance levels, and even corporate governance and management of Chinese companies operating in the United States. It is necessary to examine this system and its impact on multinational corporations' management and risk control. This article examines the impact and risk mitigation strategies surrounding Deferred Prosecution Agreements (DPAs) in the context of multinational corporate compliance, focusing on their application within the United States. DPAs serve as crucial instruments for resolving allegations of corporate misconduct while enabling companies to evade criminal prosecution under specific conditions. However, the repercussions of DPAs extend beyond individual cases, significantly influencing corporate compliance practices on a global scale. Understanding the nuanced impact of DPAs on multinational corporations is imperative for corporate executives, compliance officers, and regulatory authorities. This article elucidates the multifaceted implications of DPAs, exploring their effects on corporate governance, regulatory compliance, and corporate reputation management. Additionally, it delves into effective risk mitigation strategies that corporations can employ to navigate the complexities of DPA enforcement and enhance their compliance frameworks. Through the analysis of case studies, regulatory trends, and best practices, this article provides actionable insights for stakeholders navigating the intricate landscape of corporate compliance and regulatory enforcement in the modern era.